Antara Layanan Publik dan Premanisme: Perilaku Juru Parkir di Jalanan Sibuk Jember - Ramadhani, Rizka; Nusanto, Baktiawan (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2026)
The prevalence of illegal parking in urban areas indicates weak local parking management and supervision, a condition exacerbated by the continuous growth of private vehicle ownership. This situation has intensified social conflicts between parking service providers particularly informal parking attendants and vehicle users. This study aims to examine the nature and extent of social problems arising from interactions between parking attendants and vehicle users, with findings expected to inform local and regional policy making in developing fair and inclusive parking management regulations. This research employs a qualitative method with a case study approach to capture the specific and contextual dynamics of parking practices in Jember Regency. Data are collected through in-depth interviews with purposively selected informants and expanded using snowball sampling to ensure comprehensive and in-depth information. The findings reveal that parking practices in busy areas of Jember Regency involve two main actor groups: (1) official parking attendants coordinated by the Transportation Department, and (2) unofficial (informal) parking attendants affiliated with local businesses. Nevertheless, both groups tend to exhibit practices associated with gangsterism, which are interpreted as forms of social resistance against unequal social structures. Their practices are therefore understood not merely as legal violations, but as social expressions of inequality in access to formal employment and legitimate economic space.